Public Choice and Happiness - Bruno S. Frey; Alois Stutzer (Center for Research in Economics, Management and the Arts (CREMA), 2017)
In this contribution, we first discuss how the analysis of self-reported measures of subjective well-being can contribute to a better understanding of the extent to which public choices serve individuals' preferences. Our research insights will be drawn from the analysis of the well-being consequences of alternative institutional arrangements, the assessment of specific policies, the study of procedural utility, as well as the testing of theoretical predictions derived from models of the political process. Second, we adopt a reverse perspective and discuss how the application of insights from public choice analyses can inform and inspire happiness research on issues related to public policy. In particular, happiness indicators provide new and complementary information about the satisfaction of citizens' preferences, which will strengthen democratic competition. However, the happiness approach also has clear limitations if it is understood as a decision rule for good policy and the interaction between citizens and the government is reduced to monitoring reported happiness.
Keywords: D72; I31; 330; happiness; public choice; public policy; subjective well-being